Double learning: Who is learning from online reviews?. (24th October 2011) - He, Ling; Liu, Ling; Qin, Li; McCartney, Mark
Online user reviews have become an important source of information for consumers seeking to make the best purchase decisions possible in an online environment. Based on data collected from the online retailer website Amazon.com, this study explores the potential opportunity provided by online reviews that vendors can use to evaluate their own products and possibly make price adjustments. Using portfolio methodology, this study addresses how vendors view online ratings as quality indicators and how a change in online ratings can lead to an increase or decrease in price. The paper concludes that vendors respond to online reviews of quality and tend to fine tune the price of their products accordingly in order to increase sales revenue.